Industri Batik Tarancak Di Kampung Jawa Kota Solok (2014-2022) - Tasya Eka Putri; Etmi Hardi (Jurusan Sejarah FIS UNP, 2023)
This research is a study of industrial history that discusses the Tarancak Batik Industry in Kampung Jawa Kota Solok in 2014 – 2022. The research objective is to find out the background of the establishment of the Tarancak Batik Industry in Kampung Jawa and the development of the Tarancak Batik Industry in Kampung Jawa in 2014 – 2022. This study uses the historical method which consists of four steps, namely heuristics (source gathering), verification (source criticism), interpretation (interpretation) and histotiography (writing). The results of this study are that the Tarancak Batik Industry is the first batik industry in Solok City which was founded by Mimi on January 2, 2014. The background to the establishment of the Tarancak Batik industry was caused by economic, cultural and social factors. The Tarancak Batik industry has been able to survive and develop until now because Mimi and husband Nanang Suhardis have the ability to think creatively and innovate to create new, modern and unique works. Ability to adapt quickly and see opportunities that exist. The development of the Tarancak Batik Industry cannot be separated from product marketing and promotion using social media, participating in exhibitions and competitions. However, the use of social media and the marketplace has not been maximized because there is no one to manage it. Keywords: Industry, Tarancak Batik, Development